2014
DOI: 10.1194/jlr.m054072
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase-catalyzed transformation of epoxy fatty acids to hydroxy-endoperoxides: a potential P450 and lipoxygenase interaction

Abstract: The oxygenation reactions of polyunsaturated fatty acids include several examples in which different enzymes collaborate in synthesis of the end product. The cyclooxygenases are paired with cytochrome P450s in the transformation of arachidonic acid to prostaglandin (PG) endoperoxides and on to thromboxane A 2 and prostacyclin ( 1, 2 ). A P450 and cyclooxygenase participate in the opposite order in the metabolism of P450-derived 8,9-epoxyeicosatrienoic acid (8,9-EET) by cyclooxygenase, giving epoxy-hydroxy prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…(Note that the early-eluting peaks in Fig. 3 are irrelevant to this analysis: they are fatty acid endoperoxides resulting from the further transformation of 13 S -hydroperoxy-15,16-epoxides as characterized previously [21]). The results in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(Note that the early-eluting peaks in Fig. 3 are irrelevant to this analysis: they are fatty acid endoperoxides resulting from the further transformation of 13 S -hydroperoxy-15,16-epoxides as characterized previously [21]). The results in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to hydro(pero)xy-epoxy α-linolenic acid derivatives, monocyclic endoperoxide side-products formed and are reported in detail by Teder et al [21]. Enzymatically derived 15 S ,16 R - and 15 R ,16 S -epoxy-13 S -hydroxy derivatives were co-analyzed with the product of Fg-cat from 13 S -HOTE-ω3/PhIO on SP-HPLC using a Beckman 5-µm silica column (25 × 0.46 cm) and a solvent of hexane/isopropanol (100:5, v/v) with a flow rate at 1 mL/min (Results).…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…10 Besides, EETs has been shown to be metabolized by CYP450, COX, LOX and other enzymes, producing secondary metabolites that have less well understood biological activity. For example, Teder et al 11 recently showed that 14,15-EET is a substrate for human 15-LOX-1 and murine 12-LOX, giving a mixture of isomers containing a hydroperoxy group at positions 5, 8 and 12. However, these metabolites have not been found in vivo yet and their biological significance remains unknown.…”
Section: Introductionmentioning
confidence: 99%